2009
DOI: 10.1200/jco.2008.18.9043
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Bevacizumab in the Treatment of Persistent or Recurrent Squamous Cell Carcinoma of the Cervix: A Gynecologic Oncology Group Study

Abstract: Purpose Vascular endothelial growth factor is a key promoter of tumor progression in cervical carcinoma. The Gynecologic Oncology Group (GOG) conducted a phase II trial to assess the efficacy and tolerability of bevacizumab, a recombinant humanized anti–vascular endothelial growth factor monoclonal antibody. Patients and Methods Eligible patients had recurrent cervical cancer, measurable disease, and GOG performance status ≤ 2. Treatment consisted of bevacizumab 15 mg/kg intravenously every 21 days until disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
164
1
13

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 313 publications
(186 citation statements)
references
References 25 publications
8
164
1
13
Order By: Relevance
“…A recent GOG study (GOG-204) -the largest phase III randomised trial in recurrent/metastatic cervical cancer -compared four platinum-based doublets with the reference arm of paclitaxelcisplatin, which was found to be not inferior to the three investigational arms (Monk et al, 2008). Moreover, another GOG phase II study (GOG-227C) of targeted anti-vascular therapy (bevacizumab 15 mg kg À1 ) in this patient population showed activity comparable with cytotoxics and was well tolerated (Monk et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A recent GOG study (GOG-204) -the largest phase III randomised trial in recurrent/metastatic cervical cancer -compared four platinum-based doublets with the reference arm of paclitaxelcisplatin, which was found to be not inferior to the three investigational arms (Monk et al, 2008). Moreover, another GOG phase II study (GOG-227C) of targeted anti-vascular therapy (bevacizumab 15 mg kg À1 ) in this patient population showed activity comparable with cytotoxics and was well tolerated (Monk et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A strong association between higher VEGF expression in cervical cancer and worse prognosis has been observed (75,76).…”
Section: Intracellular Signaling Kinasesmentioning
confidence: 99%
“…Bevacizumab has been tested and used in several solid tumors with favorable results. The GOG performed a phase II trial to evaluate the efficacy and toxicity of bevacizumab (15 mg/kg every 3 weeks until disease progression or prohibitive toxicity) in persistent or recurrent squamous cell carcinoma of the cervix (Monk et al 2009a). Compared to historical control data from 6 GOG trials in this disease setting, bevacizumab showed remarkable activity.…”
Section: Phase II Trialsmentioning
confidence: 99%